Developing MSME Products via Digital Marketing Training and Application to Enhance Online Marketing - Wulandari, Siska Ayu; Ridwan, Della Aprillia; Wahyudi, Reza Dwi (Jurnal Pengabdian Masyarakat, 2024)
Purpose: The economic conditions of Kembangbahu Village, Lamongan, East Java, were impacted by the COVID-19 pandemic. This research aims to reestablish those conditions, particularly for the locals who work as mushroom producers. Method: Designing a more contemporary approach to promoting mushrooms and mushroom products is the way adopted. In order to assist “Sambal Jamur” MSMEs grow to use Instagram and community empowerment to spread the word about content that can do just that. Practical Applications: In the village of Kembangbahu, the establishment and growth of “Sambal Jamur” MSMEs constitute the research's practical implementation. One goal of advertising on Instagram is to raise awareness about the importance of digital media and how to use it to build a company's identity effectively. Conclusion: The residents of Kembangbahu Village are hoping that this marketing modernization will help them recover economically from the effects of the COVID-19 pandemic. On top of that, it may teach people how to better brand their companies through the strategic use of digital media.